Hydrous minerals on Mars as seen by the CRISM and OMEGA imaging spectrometers: Updated global view. Issue 4 (24th April 2013) - Carter, J.; Poulet, F.; Bibring, J.‐P.; Mangold, N.; Murchie, S.
Abstract : [1] The surface of Mars has preserved the record of early environments in which its basaltic crust was altered by liquid water. These aqueous environments have survived in the form of hydrological morphologies and alteration minerals, including clays and hydrated salts. Because these minerals probe on Earth aqueous environments compatible with biotic activity, understanding their formation processes on Mars is of great exobiological relevance and also offers insight into Earth's now erased ancient water environments. Using remote sensing, we conducted a large‐scale investigation of the distribution, composition, age, and geomorphic settings of hydrous minerals on Mars, providing a sharpened global view of the early aqueous environments and their evolution with time. Aqueous alteration seems to have produced clays on a planetary scale but these are found to be restricted to the oldest observable terrains on Mars (∼4 Gyr). However, very diverse aqueous environments have also been found which suggest widespread, complex aqueous settings from the surface to kilometric depths, and spanning over 1 Gyr. By building a robust statistical sample of detections, the global trends inferred here attempt to provide a broad view of our current understanding of hydrous minerals on Mars and provide context for more localized, in‐depth analyses. Collectively, these trends suggest that at least transient conditions have existed on Mars which may have been favorable for pre‐biotic to biotic activity. Key Points: Mars experienced aqueous alteration on a planetary scale Hydrous mineral diversity reveals diversity of formation environments Most of the alteration took place 4 Gyr ago but still occurred 1 Gyr later